Ideation in industrial design context: the importance of group process in brainstorming / Amer Shakir Zainol ... [et al.] - Zainol, Amer Shakir; Mohd Yusof, Wan Zaiyana; Mastor, Khairul Anwar; Mohd Sanusi, Zuraidah (Universiti Teknologi MARA Cawangan Selangor, 2016)
Brainstorming is a series of procedures (rules) designed to maximize the productivity of groups engaged in idea generation by reducing production loss, popularized by Osborn, an advertising executive. The main concern in this tool is increasing creativity in an organization. This study examines two main factors, production loss and ownership of the topic that influence the performance in group brainstorming. Production loss includes activities in production blocking, social loafing and evaluation apprehension among individuals, while ownership of the topic relates to the interest of individuals in engaging the brainstorming activities especially in industrial design. Using a quasi-experimental research design, this study reports on the participation of115 groups of university students from 6 different universities. The data is analyzed at group-level. The hypotheses of this study are tested using Partial Least Squares (PLS) regression. Results reveal that out of the three dimensions of production loss, production blocking, social loafing, and evaluation apprehension, production blocking is negatively related to the group brainstorming performance whereas evaluation apprehension is positively related to the performance or group brainstorming. As expected, ownership or the topic is related to the performance too. However, social loafing is not related to the performance or group brainstorming. The results are of potential interest to educators, and researchers. This study responds 10 a call for further brainstorming research.